Secondary Management of Midface Fractures - Aman, Hessah; Shokri, Tom; Reddy, Likith V.; Ducic, Yadranko (Facial Plastic Surgery, 2019)
Secondary reconstruction of posttraumatic facial deformities has been consistently described as one of the most challenging procedures performed. Ideal primary reconstruction cannot always be achieved, and often it is complicated by severe comminution or inadequate surgical management. It also can arise because of a lack of definitive surgical repair or excessive delay of initial treatment. Complications leading to secondary deformities can occur even when craniofacial injuries are treated by experienced surgeons. Following proper surgical principles, meticulous perioperative planning, and anticipation of potential functional and aesthetic sequelae limit many of those complications. Herein, we discuss secondary procedures in traumatic midface injuries.
Keywords: midface fractures; complications; naso-orbitoethmoidal fractures; zygomatic complex